2021
DOI: 10.24200/jonus.vol6iss1pp199-221
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality and Language Proficiency on Esl Learners' Word Contributions in Face-to-Face and Synchronous Online Forums

Abstract: Background and Purpose: Recent technological advancements and Covid-19 pandemic have prompted more opportunities for online learning. However, there is a dearth of empirical research that is focused on high school students. Therefore, this study aims to obtain a more comprehensive view of ESL learners’ involvement or word contributions in a ‘normal’ face-to-face situation and in a synchronous online text-based environment by relating it to their personality and language proficiency.   Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Nevertheless, different types of learners will benefi t from the social media platform, including those who are introverted and reticent learners (Chew and Ng, 2021;Xin and Yunus, 2019;Halif et al, 2020). Introverted and reticent learners prefer to use social media to learn English rather than in the classroom as they fear being mocked by their peers, making mistakes, or being judged by others (Cunningham & Watson, 2018;Shao & Gao, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, different types of learners will benefi t from the social media platform, including those who are introverted and reticent learners (Chew and Ng, 2021;Xin and Yunus, 2019;Halif et al, 2020). Introverted and reticent learners prefer to use social media to learn English rather than in the classroom as they fear being mocked by their peers, making mistakes, or being judged by others (Cunningham & Watson, 2018;Shao & Gao, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The state-of-art technology innovations alone do not guarantee an effective learning process and outcome (Hao et al, 2021 ). Chew and Ng ( 2021 ) emphasized the importance of integrating the effects of students' personality and proficiency in their word contribution in online forums. Different personality traits, such as, introverts or extroverts, may lead to different word productions in their online discussion with the same technological tool (Chew and Ng, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chew and Ng ( 2021 ) emphasized the importance of integrating the effects of students' personality and proficiency in their word contribution in online forums. Different personality traits, such as, introverts or extroverts, may lead to different word productions in their online discussion with the same technological tool (Chew and Ng, 2021 ). Similarly, Lai et al ( 2018 ) reported that various external and internal factors influence students' perceived study engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, readers will find the book to be helpful as a starting point to build their knowledge on text-based vs. faceto-face discussion group dynamics in L2. Many of the works cited, including Chew (2013), Chew & Ng (2016, 2021, may provide ideas for future empirical research on text-based discussion as a L2 learning tool. At times, the information presented in the book would have gained clarity by making specific references to L2 proficiency levels as defined by either the Common European Framework of Reference for Languages (CEFR) or the language proficiency scale of the American Council on the Teaching of Foreign Languages (ACTFL) or equivalent.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%